Comparing 16 Different Dual–Tasking Paradigms in Individuals With Multiple Sclerosis and Healthy Controls: Working Memory Tasks Indicate Cognitive–Motor Interference - Leone, Carmela; Moumdjian, Lousin; Patti, Francesco; Vanzeir, Ellen; Baert, Ilse; Veldkamp, Renee; Van Wijmeersch, Bart; Feys, Peter (Frontiers in Neurology, 2020)
Background. Cognitive-motor interference (CMI) is measured by dual-tasking (DT), which involves motor and cognitive tasks. There is no consensus as to whether CMI is present in Multiple Sclerosis (MS). Objectives. We investigated the effects of 16 DT conditions by measuring motor complexity, cognitive domain, and task difficulty. Method. In total, 40 pwMS with Expanded Disease Disability Scale (EDSS) 3.2±1.7 and 31 age- and sex-matched healthy controls (HC) completed 2 single walking, 8 single cognitive, 2 complex walking tasks, and 16 cognitive-motor DT. The main outcomes were mean values of gait velocity and the percentage change from single to DT (motor DT costs, mDTCs), and mean values of cognitive task accuracy and the percentage changes (cognitive DTC, cDTC). Results. Two-way ANOVAs showed the main effect of cognitive task yielded an F ratio of F(4, 268) = 72.35, p < .01 for mean gait velocity, and an F ratio of F(4, 304) = 17.12, p value < .001, for mDTC, indicating that the mean velocity was significantly lower and the mDTC significantly higher for DS_B (M=1.27, SD =.03, and M=13.52, SD=1.28 respectively). The main effect of cognitive task yielded an F ratio of F(4, 116) = 84.32, p=< .001, with the lowest average accuracy for DS_B (M = 43.95, SD= 3.33); no effect was found for cDTC. In pwMS the EDSS accounted for 28% (F=13.65, p=.001) of variance in a model predicting the highest mDTC. Conclusions. Overall, among different cognitive tasks added, the digit span backward was the most interfering cognitive task over gait velocity and accuracy. The effect was similar independently from the motor complexity and the group. PwMS and HC behaved in a similar manner at all motor complexity levels and during all cognitive task.